UMPSAs Pilgrimage Programme honours excellent B40 students - Zainal, Bahari; Naqiah, Puaad (UMPSA, 2024)
KUANTAN, 10 February 2024 - Lieutenant Colonel Professor Ir. Ts. Dr. Ahmad Ziad Sulaiman, the Deputy Vice-Chancellor of Academic and International Affairs at Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), welcomed outstanding B40 students through the recent UMPSA Love Pilgrimage Programme.